EDUCATION VALUE AND FOLKLORE CULTURE PAU-PAU RIKADONG PRINCESS TADDAMPALlE - -, Juanda (Journal of Humanity, 2013)
This article elaborates education value and cultural in folklore Pau-pau Rikadong, Princess We Taddampalie which is one of folklore in South Sulawesi. This research problem is education values and culture what is there is in folklore Pau-pau Rikadong?" This research aim to give analysis and understanding of education values and cultural in folklore Pau-pau Rikadong, Princess We Taddampalie with objective approach. Method applied in this research is descriptive qualitative. Book study data collecting method. Primary data source from free translation book. Secondary data in the form of information from book and informant. Education value and culture which there is in folklore Pau-pau Rikadong, Princess We Taddampalie, that is: deliberation of general consensus; majors throng than own self or family; compliance to old fellow; helpful; faithfulness; mutual assistance ; yields to God destiny; respects guest; and keeps a promise.Â